Assessment of the development of cereal diseases when applying resource saving soil tillage systems and using biopreparations in adaptive landscape crop farming - L. M. Kozlova; E. N. Noskova; F. A. Popov (Аграрная наука Евро-Северо-Востока, 2020)
The article presents the results of studies of complex effect of biopreparations use during basic and pre-sowing soil tillage on root rot damage and leaf and stem infections of spring grain crops (wheat cv. Svecha, barley cv. Lel’, oats cv. Selma). Studies of 2010-2017 were carried out in seven-field crop rotation on sod-podzolic medium-loam soil. The root rot damage of spring wheat was significantly lower (17.9 %) by surface tillage than by ploughing (22.5 %) in arid conditions with insufficient productive moisture (9.1-17.2 mm) and an increase in soil density (1.37-1.43 g/cm3). Under optimal humidification conditions, the differences in root rot damage of barley are equaled (21.3 and 22.4 %). High soil density (1.32-1.36 g/cm3) also caused an increase in the number of diseased oat plants by surface tillage (21.6) compared to ploughing (14.6 %). Treatment of crops with the preparations Streptomyces castelarensis А4 and Pseudobacterin-2 in the tillering phase led to a significant decrease in root rot damage only on oats (by 17.1 and 17.4 %, respectively). The degree of damage of spring grain crops with leaf and stem diseases was not significantly affected by the methods of basic and pre-sowing tillage. Only the use of a combined sowing unit for cultivation of spring wheat reduced the damage with leaf rust by 2.9 %, with septoriosis – by 1.0% compared to the control. On wheat, the preparations were effective on the background of ploughing reducing leaf rust damage by 15.2 and 11.6 %. The preparation S. castelarensis А4 had a greater effect on barley: the number of plants affected by crown rust was 19.1% less. Pseudobacterin-2 had a better effect on the background of surface tillage, reducing the incidence by 12.9 % relative to the control (ploughing to 20-22 cm). On oat sowings, the preparations were comparable in effect: the intensity of crown rust damage was significantly lower by 5.0 and 4.7 % compared to the control. The action of S. castelarensis А4 is more effective on the background of surface soil tillage. Pseudobacterin-2 had the best effect by plowing. The damage of wheat with stem rust and septoriosis was low. Thus, the methods of basic tillage did not affect the damage of grain crops with leaf and stem diseases and significantly decreased the development of root rot in wheat and oats. Methods of pre-sowing tillage did not have a significant effect on the damage of spring grain crops with root rot and significantly reduced the damage of wheat with leaf rust and septoriosis. The preparations used reduced the intensity and the development of root rot of oats and leaf and stem diseases of wheat, barley, oats.